Childhood and Adulthood Rural Residence Increases the Risk of Dementia: NEDICES Study - Contador, Israel; Bermejo-Pareja, Felix; Puertas-Martin, Veronica; Benito-Leon, Julian (Current Alzheimer Research, 2015)
Objective. This research aims to determine whether residence (rural vs. urban) at different life stages (childhood, adulthood, and late life) is associated with increased risk of incident dementia in a population-based cohort of older Spaniards. Methods. In this prospective study, 2,711 participants aged 65 years and older were assessed at baseline and 3 years later. All cases of incident dementia were diagnosed using DSM-IV criteria. The relationship between residence and the relative risk of dementia was analysed using Cox's regression models. Demographics, comorbidity index, consumption (tobacco / alcohol) and doubtful dementia diagnosis were considered as possible confounders. Results. At the three-year follow-up, 91 cases of dementia were detected. Lower education and occupational attainment were associated with a higher incidence of dementia three years later. Rural residence in adulthood was associated with a significantly higher risk of dementia at the follow-up. Childhood rural residence revealed a marked trend for risk of dementia (p = 0.08), but it was nonsignificant in later life. The risk of dementia was considerably higher for the rural/low-education group than for the urban/high-education group, for both childhood and adulthood residence. Finally, people from areas with the lowest socio- economic status Arévalo (rural, blue-collar) and Margaritas (urban, blue-collar) showed higher risk of dementia than people from Lista (urban, mixed white/blue collar). Conclusion. In this cohort, early and mid-life stages rural residence was a risk factor for dementia, but not later-life rural residence. The rural residence effect was noticeably higher in people with a lower educational level.
Keywords: Cognitive reserve